2014
DOI: 10.1055/s-0034-1379017
|View full text |Cite
|
Sign up to set email alerts
|

l-Proline-Catalysed Unusual Product Formation from the Reaction of 4- Hydroxydithiocoumarin and Aldehydes through a Pseudo-Three-Component Reaction

Abstract: A convenient and highly efficient synthetic protocol is reported for the synthesis of hitherto unreported thiopyrano{2,3b:6,5-b′}bis(thiochromene)-12,14(13H)-diones by a domino pseudo-three-component reaction utilizing 4-hydroxydithiocoumarin and aldehydes. Single-crystal X-ray crystallographic analysis of the 13-phenyl-12H-thiopyrano[2,3-b:6,5-b′]bis(thiochromene)-12,14(13H)dione derivative shows a layered structure that is stabilized by the unexpected C-S•••π interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…4 Earlier, we noted that the reaction of 4-hydroxydithiocoumarin and aromatic aldehyde using 10 mol% l -proline as a catalyst generated a pentacyclic molecule through the Knoevenagel reaction via a pseudo-three-component reaction depicted in Scheme 1a. 5 We have also observed that 4-hydroxydithiocoumarin reacts with β-nitrostyrene, which acts as a Michael acceptor, to provide an unusual oxime product as summarised in Scheme 1b. 6 The present study intends is to investigate whether cinnamaldehyde will behave similar to aromatic aldehyde or the reaction behavior will be like that of β-nitrostyrene products.…”
Section: Introductionmentioning
confidence: 85%
“…4 Earlier, we noted that the reaction of 4-hydroxydithiocoumarin and aromatic aldehyde using 10 mol% l -proline as a catalyst generated a pentacyclic molecule through the Knoevenagel reaction via a pseudo-three-component reaction depicted in Scheme 1a. 5 We have also observed that 4-hydroxydithiocoumarin reacts with β-nitrostyrene, which acts as a Michael acceptor, to provide an unusual oxime product as summarised in Scheme 1b. 6 The present study intends is to investigate whether cinnamaldehyde will behave similar to aromatic aldehyde or the reaction behavior will be like that of β-nitrostyrene products.…”
Section: Introductionmentioning
confidence: 85%
“…Over the years, it has been known that bis-lawsones have numerous biological activities as well as cosmetics applications. Khan and co-workers 14 reported a novel domino pseudo-MCR to synthesize thiopyrano{2,3- b :6,5- b ′}bis(thiocromene)-12,14(13 H )-diones 11 involving a Knoevenagel condensation/Michael-type addition, followed by intramolecular cyclization and loss of H 2 S ( Scheme 1b ). Using the same method, Naime-Jamal and Ghahremanzadeh 15 synthetized the 3,3′-bis-substituted-2-oxindoles 12 using cyclohexyl isocyanide ( Scheme 1b ).…”
Section: Pseudo-three Component Reactionsmentioning
confidence: 99%
“…[8] In our earlier observation, it was reported that the reaction of 4-hydroxydithiocoumarin and various aldehydes could produce a pentacyclic product having 3 sulfur atoms in the ring. [9] On the other hand, Popowycz et al reported a similar reaction using 4-hydroxycoumarin as the starting material, which produced a dimer without ring closure. [10] Our intention for the present study is to determine whether the reactivity pattern of 4-hydroxythiocoumarin follows either the chemistry of 4-hydroxycoumarin due to its similarity at position 1 and 4 or that of 4-hydroxydithiocoumarin (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group demonstrated the chemistry of another thio analogue of 4‐hydroxycoumarin, namely 4‐hydroxydithiocoumarin, in synthesizing numerous new molecules, which have recently been reviewed [8] . In our earlier observation, it was reported that the reaction of 4‐hydroxydithiocoumarin and various aldehydes could produce a pentacyclic product having 3 sulfur atoms in the ring [9] . On the other hand, Popowycz et al.…”
Section: Introductionmentioning
confidence: 99%